SOSIALISASI SADAR WISATA DAN BAKTI SOSIAL BAGI MASYARAKAT DESA WISATA BAKAU SERIP KELURAHAN SAMBAU KECAMATAN NONGSA, KOTA BATAM - Wahyudi Ilham; Dailami; Tirta Mulyadi (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
The development of the tourism sector has a relationship with the economy which aims to improve the welfare of local people living around tourist sites. The creative industry through tourism has a different form with the typical elements of culture and traditions of the village that has the tourist location. The process of developing tourism villages requires an institutional role as a forum in collecting aspirations and supporting the success of the tourism sector. Conscious tourism is a fundamental thing that must be understood by every walk of life. High tourism awareness encourages people to actively participate in tourism development. Efforts to increase tourism awareness for the community in the Bakau Serip tourism village are very important, because this village is developing tourism. Bakau serip tourism village has a very strong tourism potential, but it has not been supported by the readiness of human resources. In addition, the level of tourism sandar of the Bakau Serip community is also still very low. This community service is one of the efforts to increase the understanding and quality of human resources in order to increase tourism awareness. The methods used are lecture techniques and participatory approaches. The community is directly involved in the training through interactive discussions. From the results of this training, the community has a strong understanding of the importance of developing tourism villages and raising awareness to be actively involved in the management of tourism villages. Social service or better known as social service is an activity a form of concern or humanity towards fellow humans. Where with this activity we can glue our sense of kinship towards others. The word social includes individuals and groups. Filial piety can be interpreted as binding (binding) oneself to oneself or other selves. This bond is in the form of care, a feeling of responsibility for the lives of others. Social service can mean giving something (to those who need giving).